A weakly solvating electrolyte towards practical rechargeable aqueous zinc-ion batteries - Xin Shi; Jinhao Xie; Jin Wang; Shilei Xie; Zujin Yang; Xihong Lu (Nature Communications)
Abstract Structure deterioration and side reaction, which originated from the solvated H2O, are the main constraints for the practical deployment of both cathode and anode in aqueous Zn-ion batteries. Here we formulate a weakly solvating electrolyte to reduce the solvating power of H2O and strengthen the coordination competitiveness of SO4 2− to Zn2+ over H2O. Experiment results and theoretical simulations demonstrate that the water-poor solvation structure of Zn2+ is achieved, which can (i) substantially eliminate solvated-H2O-mediated undesirable side reactions on the Zn anode. (ii) boost the desolvation kinetics of Zn2+ and suppress Zn dendrite growth as well as structure aberration of the cathode. Remarkably, the synergy of these two factors enables long-life full cells including Zn/NaV3O8·1.5H2O, Zn/MnO2 and Zn/CoFe(CN)6 cells. More importantly, practical rechargeable AA-type Zn/NVO cells are assembled, which present a capacity of 101.7 mAh and stability of 96.1% capacity retention after 30 cycles at 0.66 C.